Transforming Indonesian Literature Learning through Virtual Reality and Augmented Reality - Septiaji, Aji; Nurhidayat, Eka; Miftahudin, Iip; Choerunnisa, Nanis Regina (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The development of digital technology has opened new opportunities in developing literary learning models, particularly through the utilization of Virtual Reality (VR) and Augmented Reality (AR). This study aims to examine the transformation of Indonesian literature learning through the integration of VR and AR technologies. Using a qualitative approach and library research methods, this study analyzes various literature sources that discuss technology-based learning innovations and their implications for improving literary literacy. The study results indicate that virtual reality technology allows students to